POPE FRANCISK IN CAIRO. ANALYSIS OF THE BRAND OF PONTIFF ON THE INSTAGRAM - Materian, Esther (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Instagram is one of the most popular social networks with more than 1.14 billion users worldwide. It was designed for mobile taking, editing and sharing photos. Today, many use Instagram which attracts millions of followers. Pope Francis is one of the most prominent contemporary religious figures. This study, based on publications of the visit to Cairo, explores the way the head of the Catholic Church uses Instagram to design a personal brand supporting his authority. Mobile devices and applications used on the same principle as Instagram invites new audiences and new interactions of religious leaders and their public. Accordingly, this article offers new proposals for studying the relations between religious leaders and the authorities in the media age. The aim of the research is to investigate the impact of the use of social networks by religious leaders, in particular the head of the Catholic Church, Pope Francis. Research methods: in the course of the research comparative, philosophical and logical methods, as well as the method of user identification in different social networks and the method of analysis were used. Research results. The publications of Pope Francis during a visit to Cairo were used to analyze how he creates a personal brand on Instagram. The relation of Instagram brand to the formation of Pope’s authority and his interaction with the audience. The analysis of sources showed that in the Ukrainian scientific community there is very little religious and sociological research on the impact of social networks on the formation of a brand of religious leaders, as well as on the use of these technologies to interact with the target audience. Discussion. Among the European works covering religion and media technologies there are the works of K. Kravalo (University of Tilburg), D. Huzak (University of Silesia), M. Abdel-Fadil (University of Oslo), D. Luddickens (University of Zurich), G. Stewart (University of Pennsylvania). Conclusion. Pope Francis' two Instagram posts during his visit to Cairo show the world Christian leader embracing a powerful Muslim leader. In the Coptic Church, the Pope lights a candle, and photographers capture every movement. Posting these points on Instagram strengthens his position in the public debate on the relationship between Christianity and Islam. The fact that he has received thousands of likes, made a significant contribution to his publicity and influence. On Instagram, his authority is being legitimized by the attention he receives much more than most religious people on social media. And the question of whether the meaning of the Pope's publications can strengthen or change the worldview of his followers remains open and needs further study.